La enseñanza de la atención farmacéutica en pregrado: la experiencia de una universidad de los EEUU de américa - Arce M., Lillian (2005)
The practice of Pharmacy continues to evolve from its traditional role of dispensing medication toward the management of use of pharmaceutical products in disease states, for which cost-effective pharmaceutical services are reimbursed. The goal of the Patient Care Management Courses is to provide the student the opportunity to integra te and practice all aspects of pharmaceutical careo For two semesters, third year students at local and distant sites take the courses that combine lectures and hands-on laboratory exercises. These courses consist of one-hour lecture per week and a three-hour laboratory on alternating weeks for the total of 15 weeks during the fall semester, and 14 weeks in the spring semester. Lectures review the top 200 drug products by presenting the students wíth disease-state based c1ínical situations encountered prímarily in the community setting. Areas covered include diabetes, asthma, and hypertension, among others. Each laboratory session is staffed with three experienced c1inical pharmacists, and 20-24 students divided into groups of four per working table. The «Patient Care Management Lab" manual is required for laboratory sessions. Students are assessed for identification of therapeutic problems, patient counseling, and tasks such as interpreting prescriptions and typing labels. In preparation for future in-service presentations, each student present two assigned drugs in class, focusing on management of drug therapy,detection and evaluation of medication-related problems. Students are videotaped while they counsel «patients» for self-evaluation. These courses, designed to educate our future clinicians about practical issues associated with current and future pharmacy practice, are standardized for uniformity among sites.